Solid Waste Management in Ghana: The Case of Tamale Metropolitan Area - Puopiel, Felix (2011)
A Thesis submitted to the Department of Planning Kwame Nkrumah University of Science and Technology in Partial Fulfilment of the Requirements for the Degree of MASTER OF SCIENCE IN DEVELOPMENT POLICY AND PLANNING.